Case report: “Congenital cutaneous langerhans cell histiocytosis presenting with blueberry Muffin Rash” - Thalji, Mariam; Yagmour, Asil; Alameh, Dania; Shatrit, Hanin; Inerat, Mais; Bannoura, Sami Issa; Atawneh, Amir; Abuawaad, Motee (Frontiers in Pediatrics, 2022)
Congenital cutaneous Langerhans cell histiocytosis-(LCH), named Hashimoto Pritzker disease, is a rare subtype among the clinical spectrum of LCH that often presents at birth or through the neonatal term and spontaneously resolve within a few months. In rare instances, infants with congenital cutaneous LCH may present with a blueberry-muffin rash. We reported a case of a male newborn who presented with blueberry muffin rash and was diagnosed with congenital cutaneous LCH later on. The diagnosis was confirmed by excluding other possible systemic causes of blueberry muffin rash, followed by a skin biopsy. Skin biopsy showed reticular dermis-hypodermis infiltration by medium-sized cells which have a pale eosinophilic cytoplasm and irregular nuclei. The lesional cells were positive for Langerin, CD1a, S100, and CD68 immunostains, consistent with congenital cutaneous LCH. Follow-up revealed no recurrence of the cutaneous lesions or any systemic involvement, which further leads to congenital cutaneous LCH diagnosis. Even though it is very rare, blueberry muffin rash differential diagnosis should include congenital cutaneous LCH. Early recognition of this condition protects patients from unnecessary and possibly unsafe systemic treatment.